PENGARUH ELECTRONIC WORTH OF MOUTH TERHADAP CITRA PERUSAHAAN GADGET DI KOTA BATAM - Golan Hasan; Karina Karina (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2021)
In conducting of this research, has the purpose of knowing the factors that influence purchase intention. eWOM Credibility, eWOM Quality, eWOM Quantity, Corporate Image as mediating role are factors that will be examined and analyzed. The object of this research is smartwatch that ocated in Batam City with certain criteria that using media social active. Purposive sampling is the method in this study, selected are adjusted to the research objectives. The data analysis in this research is  PLS-SEM (Partial Least Square Structural Equation Modelling). The result of this research is indicate that the eWOM Quality, eWOM Quality, Corporate Image are able to influence significantly on Purchase Intention while eWOM Credibility doesn’t have a strong effect and maybe influence by other variables on Purchase Intention. In addition Corporate Image’s able to mediate eWOM Credibility, eWOM Quality, eWOM Quality and Purchase Intention.